MANAJEMEN PESERTA DIDIK DI LEMBAGA PENDIDIKAN - Muli Prima Aldi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2022)
Education is a process of humanization through the appointment of human beings to the human level. That is, education is to bring people out of ignorance, by opening the actual-transcendent veil of human nature (humannes). The learning process also requires efforts to understand how individuals are different from others (individual differences). On the other hand, understanding how to be human like other humans (equality in specieshood or humanes). The educational process should provide an inside out place for self-empowerment based on one's own paradigm, character and motives. With self-awareness and self-insight, students can "connect" with themselves and have a deeper understanding of themselves.